Israel and the Palestinian refugee issue - Tobi, Jacob., author.
1 online resource (xvi, 306 pages)
Keywords: "Examining the development of Israel's policy toward the Palestinian refugee issue, this book spans the period following the first Arab-Israeli War until the mid-1950s, when the basic principles of Israel's policy were finalized. Israel and the Palestinian Refugee Issue outlines and analyzes the various aspects that, together, created the mosaic of the "refugee problem" with which Israel has since had to contend. These aspects include issues of repatriation, resettlement, compensation, blocked bank accounts, internal refugees and family reunification. Drawing on extensive archival research, this book uses documents from Israeli government meetings, from the Foreign Affairs and Defense Committee and files from the office of the Prime Minister's advisor on Arab affairs to address the many diverse aspects of this topic, and will be essential reading for academics and researchers with an interest in Israel, the Middle East, and political science more broadly"-- "This book recounts the narrative of how Israeli policy towards the Palestinian refugee problem was formulated from the time it first developed at the beginning of 1948, following the first Arab-Israeli war ("Israel's War of Independence"), until the mid-1950s, when that policy's basic principles were shaped in their final format and concluded. This volume outlines and analyzes the various issues, which together created the mosaic of the "Palestinian refugee problem", and with which Israel has had to contend since then, i.e., repatriation, resettlement, compensation for abandoned property and blocked bank accounts, the internally displaced refugees and family reunification"--